2016
DOI: 10.1093/schbul/sbw129
|View full text |Cite
|
Sign up to set email alerts
|

Redox Dysregulation in Schizophrenia Revealed by in vivo NAD+/NADH Measurement

Abstract: Balance between the redox pair of nicotinamide adenine dinucleotides (oxidized NAD+ and reduced NADH), reflects the oxidative state of cells and the ability of biological systems to carry out energy production. A growing body of evidence suggests that an "immuno-oxidative" pathway including oxidative stress, mitochondrial dysfunction, neuroinflammation, and cell-mediated immune response may contribute to disruptions in brain activity in schizophrenia (SZ). The aim of this study is to assess possible redox imba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 48 publications
7
76
0
1
Order By: Relevance
“…A converging body of evidence has suggested a role for oxidative stress and altered antioxidant defenses in psychotic disorders (Yao and Keshavan, 2011). In a recent study, we found evidence of a significant reduction in NAD+/NADH measured by 31 P MRS, reflecting redox imbalance, in the brain of patients with first episode and chronic schizophrenia (Kim et al, 2017), compared to healthy controls. To our knowledge, no studies have previously measured NAD metabolites using 31 P MRS in unaffected relatives of patients with psychotic disorders.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…A converging body of evidence has suggested a role for oxidative stress and altered antioxidant defenses in psychotic disorders (Yao and Keshavan, 2011). In a recent study, we found evidence of a significant reduction in NAD+/NADH measured by 31 P MRS, reflecting redox imbalance, in the brain of patients with first episode and chronic schizophrenia (Kim et al, 2017), compared to healthy controls. To our knowledge, no studies have previously measured NAD metabolites using 31 P MRS in unaffected relatives of patients with psychotic disorders.…”
Section: Introductionmentioning
confidence: 89%
“…Patients, siblings and controls were excluded if they had a history of significant medical or neurologic illness, history of significant head trauma, contraindication to MR scan (including claustrophobia) or pregnancy. Of note, the unaffected sibling data we present here is entirely new, but 28 patients and 11 controls in this analysis overlap with the study population in our recent study (Kim et al, 2017), and we include them for comparison purposes. The study was approved by the McLean Hospital Institutional Review Board, and participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations